Climate and the Chronology of Iranian History. Issue 6 (November 2016) - Amanat, Abbas; Tahbaz, Morad; Bayani, Niloufar; Cole, Camille; Mikhail, Alan
Abstract : This article offers a chronology of climate events in Iran over the last millennium to challenge traditional chronologies of the Iranian past based on politics, war, and economics. Using insights gleaned from the historiography of climate in Iran, and from neighboring regions, especially the Ottoman Empire, four episodes of climate cooling show how climate-induced environmental processes affected more people for longer in Iran than did the policies of the empires ostensibly ruling over them. Thus, the article aims to put climate more squarely on the agenda of historians of Iran so that the conjectures advanced here can be confirmed, revised, or discarded through future empirical research. Moreover, the article seeks to bring Iran into wider conversations in environmental and global history.